Determinación de Hidatidosis en Bovinos faenados en el Camal Municipal del Cantón Ventanas - Ramos Briones, Sara Elizabeth (2023)
In the canton of Ventanas, province of Los Ríos, Ecuador, there is a lack of knowledge about the incidence of hydatidosis, a zoonotic parasitic disease caused by the juvenile form of the helminth Echinococcus granulosus, which causes a risk to the health of animals and humans. The objective of this work was focused on determining the presence of bovine hydatid cysts in bovines that are slaughtered in the Municipal Camal of the Ventanas canton. The research study was carried out in order to provide updated statistics on the presence of hydatid cysts in the viscera and carcasses of these food animals, determined by post-mortem inspection at the slaughterhouse. In addition, it was established to characterize the positive bovines according to the variables studied, such as; sex, age, race, place of origin and affected organs. The sample size was 300 cattle, the methodology used in data processing was the non-parametric statistical design (Chi Square), and the methods were inductive - deductive, inductive and the experimental method. Therefore, the incidence obtained was 1.67% in the bovine liver, the highest presence of hydatid cysts was in males with 1.94%, while the breed that presented the highest incidence was the mestizo with 13.8 %; of the 3-year-old category with 2%; the provenance that presented a high incidence was Caluma with 11.11%, and the most preferred organs affected by the parasite were the lungs, representing 1.33%.